Study of prevalence of maternal anaemia and its fetal outcome at rural tertiary care centre - Verma, Vandana; Vishwakarma, Soniya; Chand, Ramesh; Gupta, Umesh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anaemia is a major public health problem especially among low socioeconomic class of the population in developing countries. Prevalence of anaemia among pregnant women in developing countries is 51%. Anaemia is defined by the WHO as haemoglobin levels of less than 11 gm. % in pregnancy. The present study was aimed to find out prevalence of anaemia in rural tertiary care centre to see the foetal outcome in anaemic women. Methods: This is a retrospective observational study done in the Department of Obstetrics and Gynaecology, University of medical sciences Saifai, Etawah from June 2017 to November 2017. All the women admitted to labour room in third trimester and delivered here were included in the study excluding the patients with pre-eclampsia, eclampsia, gestational diabetes mellitus, heart disease, patients with other medical disorders and patients with twin pregnancy, antepartum haemorrhage and the patients who did not deliver here. Results: Prevalence of anaemia was 87.3 %. severe anaemia was found in 3.5 % women. The percentage of preterm births was more in anaemic women that is 16.9 %. Conclusions: Anaemia in pregnancy is a major public health problem in India. The number of IUGR and LBW babies were more in anaemic women. Anaemia is related to serious consequences in mother and baby if not diagnosed and treated timely. It can be prevented by increasing the awareness regarding need of iron intake during pregnancy.